Configuração espacial e qualidade física de parques urbanos lineares: o caso do Parque Parahyba I, João Pessoa-PB - Lima, Larissa Ellen Oliveira de (2022)
The recurring themes on urban parks have different approaches, developed in an interdisciplinary and multidisciplinary way. Some researches discuss the relationship between physical activity and green areas, as well as their associations with the well-being and effects on the health of the population, others, with greater emphasis on environmental and ecological aspects. However, it is noted that there is still a need for in-depth research on the physical and spatial attributes of urban parks, especially in studies of linear typology parks. In this sense, this research investigated the physical type and analyzed the physical quality and the spatial configuration of Parque Parahyba I (João Pessoa-PB), as an example of a linear urban park. We sought to discover the degree of quality of the park and understand the spatial configuration, using the adapted CPAT tool. Four dimensions of analysis were used as the guiding thread of the research, namely: (1) access and neighborhood; (2) areas of activities; (3) features and security; and (4) spatial configuration. In this way, the study proposes reflections and provides premises for the understanding of the attributes and physical conditions of this park and for the practice of projects of this nature in contemporary cities. Thus, through an adapted methodology, indicators were obtained that analyzed the degree of physical quality of the object of study, considering its specificities. The four analytical dimensions were classified in scores from 0 to 1, which correspond to conditions that vary from 'very bad' to 'excellent', where each one of them has a degree of adequacy and intervention in the space. The results show that the dimension of resources and security, and access and neighborhood, both with means equivalent to 0.62 (zero point sixty-two), had the lowest value. The dimension of areas of activities had the final value of 0.78 (zero point seventy-eight). These three dimensions were classified as good conditions, but they need interventions, with action in the medium term. The spatial configuration dimension had the highest value, with 0.83 (zero point eighty-three), classified as excellent condition, with no need for immediate intervention.